Natural Resource Dependence and Tax Effort in Sub Saharan Africa (2022)
The study investigated the empirical relationship between natural resource dependence and tax effort in 28 Sub-Saharan African countries, with data for the period 1996-2016. The findings indicated that in economies with oil rents, less efforts is invested on other non-oil-resource revenues. In these countries, trade openness deteriorates tax revenue efforts, consequently the bulk of government revenue come from the sale of crude oil. In contrast, economies without oil rents seem to channel more efforts towards non-oil-tax revenue. In these economies, our result showed that trade openness is an important improvement to tax revenues. We recommend that for economies with oil rents, proper tax record keeping and documentation of separate revenue sources be maintained. Conversely, other resources rent economies are also recommended to depend less on natural resources rents and grants from foreign donors; and maintain a policy of no non-tariff barriers to trade, except for health, social and security reasons.